89 CSF BIOMARKER UTILITY IN SUPPORTING ALZHEIMER'S DISEASE DIAGNOSIS: CLINICAL PERSPECTIVES FROM AN IRISH REGIONAL SPECIALIST MEMORY SERVICE. (18th November 2021) - Dolphin, H; Fallon, A; McHale, C; Dookhy, J; O'Neill, D; Coughlan, T; Coveney, S; O'Dowd, S; Kennelly, S P
Abstract: Background: CSF (cerebrospinal fluid) biomarkers [amyloid- beta-42 (AB-42), phosphorylated tau (p-tau)] are increasingly used in supporting clinical diagnosis of Alzheimer's Disease (AD). Both elevated CSF p-tau and reduced AB-42 are necessary for pathological diagnosis of AD. The aim of this study is to apply recent international recommendations to patients attending a regional specialist memory service, evaluating consistency with detailed clinical, neuroimaging, and neuropsychological ad -phenotype profiling. Methods: All patients age < 80, with mild/subjective cognitive and/or atypical neurobehavioral symptoms, non-significant vascular burden on neuroimaging, and without contraindication to lumbar puncture are offered CSF analysis. Clinical diagnosis was ascribed on the basis of specialist multi-disciplinary consensus review. We undertook a case-note and database retrospective review of those who had ad -biomarker CSF analysis, collecting demographic, clinical phenotype diagnosis, and neuropsychological performance. Data was extracted and analysed using SPSS v.25. Results: One-hundred-sixteen patients underwent CSF biomarker testing. Forty-nine patients (42%) had positive AD-CSF biomarkers, 41/49 (84%) of whom presented with common ad phenotypes (Amnestic/Logopenic PPA/PCA). Twenty patients (17%) had negative ad -CSF (elevated AB-42, and low p-tau) studies, and half of those (10/20, 50%) had a consistent atypical non-AD clinical phenotype. Patients with negative ad -CSF were younger and tended to have non-amnestic neuropsychological profile. Therefore there was a mismatch in 18/69 (26%) people in these groups with definitive +/− ad biomarker results and ad /Non-ad clinical phenotype. A further forty seven (40%) patients had indeterminate CSF studies with one or other changes in AB-42 or p-tau, but not both as is necessary for definitive diagnosis. Conclusion: Incorporation of CSF biomarker analysis is quickly being established as a key component of the neurocognitive/dementia diagnostic pathway. However, there are challenges and limitations arising as they are applied in clinical settings, and further research is warranted to explore variations between pathological results and clinical phenotype presentation.